EXPLORING ENDOCRINE ETIOLOGIES OF OSTEOPOROSIS AND STRATEGIES FOR COMPREHENSIVE MANAGEMENT (International Conference on Modern Science and Scientific Studies, 2025)
This thesis explores endocrine causes of osteoporosis, such as hyperparathyroidism, hyperthyroidism, hypogonadism, and glucocorticoid excess. Advanced diagnostics help accurately identify these disorders. Treatment includes hormone-specific therapies, antiresorptive agents, and anabolic options. Addressing hormonal imbalances alongside bone-targeted interventions improves bone density and reduces fracture risk. Effective management requires a multidisciplinary, personalized approach for optimal outcomes.